THE URGENCY OF ANTI-CIRCUMVENTION ARRANGEMENTS IN INDONESIA: A COMPARATIVE ANALYSIS WITH THE UNITED STATES AND ISLAMIC LAW PERSPECTIVES - Prasetyo, Adi; Wirdyaningsih, Wirdyaningsih (Universitas Islam Negeri Mataram, 2025)
This study examines the urgency of anti-circumvention regulations in Indonesia to address the practice of circumvention that harms the domestic industry and state revenue. Circumvention, or avoidance of anti-dumping import duties in Indonesia, often occurs through diverting export routes through third countries. For example, H&I Section steel from China has entered Indonesia via Thailand. Similarly, after anti-dumping was imposed on Chinese HRC Alloy products, imports from Japan, Taiwan, and Vietnam surged. As a result, the domestic industry experienced significant sales volume and profits declines, while the country lost potential revenue. The broader impact includes reduced anti-dumping policy effectiveness, increased risk of layoffs, and factory closures due to unfair competition resulting from circumvention. This study employs qualitative normative research methods through a literature review, examining primary legal materials (such as laws and regulations from Indonesia and the U.S.), secondary sources (literature, journals, previous research results), and tertiary sources (legal dictionaries, encyclopedias). The analysis uses a comparative approach between the Indonesian and United States legal systems and examines Islamic law's perspective on these practices. The study’s findings indicate that Indonesia lacks specific regulations to address circumvention, unlike the United States, which already has a structured system. Concrete recommendations include: first, there is a need for a clear operational definition of circumvention. Second, an integrated monitoring system should be developed based on national trade data and community involvement through complaint channels. Third, the investigation procedure should allow initiation by both the authorities and external parties, with field verification and a deadline for completion. Fourth, progressive sanctions should be enforced, such as expanding anti-dumping import duties, suspending import permits, and imposing retroactive fines. Regulations can be further strengthened by adopting best practices from countries such as the United States and integrating the principles of maqashid sharia (justice, protection of property, and public welfare) so that regulations are technically effective, fair, and socially sustainable. With these measures, Indonesia can close the regulatory gap regarding circumvention, protect the domestic industry, and optimize state revenues from the international trade sector.